Urgensi Pemilihan Alat Permainan Anak Usia Dini sebagai Perangsang Perkembangan Otak Anak - Loeziana Uce (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2021)
Learning while playing can fulfill children's happiness, because children's brain growth will increase when children feel fun and happiness. Therefore, game tools are used as learning resources for children, besides the characteristics of game tools and tips for choosing them must be known by parents or teachers. The method used is a qualitative method with the type of research being literature. The results of the study indicate that the game tool is a tool designed or made to be a source of learning for early childhood in order to get a good learning experience. Some experts state that children play because they have excess energy. This energy encourages them to do activities so that they are free from feeling depressed. Furthermore, Guslinda and Kurnia argue that educational game tools are types of equipment or objects that can be used in playing where these objects can encourage and develop all children's abilities. Then the characteristics of educational game tools, one of which is a game tool that can be played with various purposes and benefits. Knowing or paying attention to the types of equipment is also very important as paying attention to the design is easy and simple. When choosing a game tool, one must choose a variety of toys. In order to avoid bad things, before choosing a game tool, observe the forms and types of games that children like.